2016
DOI: 10.1091/mbc.e15-09-0621
|View full text |Cite
|
Sign up to set email alerts
|

The alternate AP-1 adaptor subunit Apm2 interacts with the Mil1 regulatory protein and confers differential cargo sorting

Abstract: Adaptor complexes are important for cargo sorting in clathrin-coated vesicles. The µ adaptor subunits Apm1 and Apm2 create functionally distinct versions of the yeast AP-1 complex. A novel regulatory protein is identified that selectively binds Apm2-containing complexes and contributes to their membrane recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…To monitor AP-1C, we used calcofluor white (CFW) sensitivity in cells lacking the exomer subunit Chs6. This assay is thought to monitor the AP-1c-dependent retention of the chitin synthase Chs3 in the TGN when its normal traffic out of the TGN is disrupted (29,32). We found that laa2⌬ and laa1⌬ caused similar increases in the CFW sensitivity in cells lacking Chs6, suggesting a similar defect in AP-1C-mediated traffic (Fig.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…To monitor AP-1C, we used calcofluor white (CFW) sensitivity in cells lacking the exomer subunit Chs6. This assay is thought to monitor the AP-1c-dependent retention of the chitin synthase Chs3 in the TGN when its normal traffic out of the TGN is disrupted (29,32). We found that laa2⌬ and laa1⌬ caused similar increases in the CFW sensitivity in cells lacking Chs6, suggesting a similar defect in AP-1C-mediated traffic (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…The top correlated genes also included deletion of MIL1, a recently identified co-factor for AP-1, LAA1, and TRS33, a core component of the TRAPP tethering complexes that function at the Golgi and endosomes ( Fig. 1A) (29,30). The top hits also included one uncharacterized gene YBL010c; on the basis of the results described below, we refer to YBL010c as LAA2 (Large Adaptin Accessory 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeast AP-1 null mutants also have minor defects in lipid PtdIns(3,5)P2-dependent processes and show reduced ability to traffic ubiquitylated cargoes to the vacuole lumen (Phelan et al, 2006). Notably, in S. cerevisiae , there are two forms of AP-1 which share the same large (Apl2 and Apl4) and small (Aps1) subunits, but distinct medium subunits (Apm1 or Apm2) that seem to confer differential cargo recognition and sorting (Valdivia et al, 2002; Renard et al, 2010; Whitfield et al, 2016). Additionally, in yeast, the AP-1 complex seems to co-operate with the exomer, a non-essential, fungal-specific heterotetrameric complex assembled at the trans-Golgi network, for the delivery of a distinct set of proteins to the plasma membrane (Hoya et al, 2017; Anton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%